Pengaruh Lingkungan Kerja Fisik Dan Kepuasan Kerja Terhadap Turnover Intention Karyawan Pada PT Winstar Packindo Sukses - Maya Sajida; Laila Listiani Putri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - This study aims to determine the effect of the physical work environment and job satisfaction on employee turnover intention at PT. Winstar Packindo Sukses, both partially and simultaneously. The type of research used is quantitative research with data analysis methods used in this study include validity tests, reliability tests, classical assumption tests, quantitative analysis, multiple linear regression analysis, and hypothesis testing using t-tests and f-tests. The population in this study were employees of PT. Winstar Packindo Sukses with a total of 69 respondents. The results of this study indicate that the influence of physical work environment variables on turnover intention from the results of the t-test, sig. = 0.000 < 0.05 and t count (4.757) > t table (1.996), the influence of job satisfaction on turnover intention from the results of the t-test, sig. = 0.001 < 0.05 and t count (3.323) > t table (1.996), and the influence of physical work environment and job satisfaction on turnover intention from the calculated f value of 65.451 > f table 3.14, from all these variables means H0 is rejected and Ha is accepted. Thus, it can be concluded that the physical work environment and job satisfaction partially and simultaneously have a positive and significant influence on employee performance at PT Winstar Packindo Sukses.